Exploring the Role of Food in The Prime of Miss Jean Brodie - Antony HOYTE-WEST (Cultural Intertexts)
First published in 1961, Muriel Spark’s novel The Prime of Miss Jean Brodie is one of the most well-known works of 20th-century British literature, and the book’s portrayal of the eponymous Edinburgh schoolmistress and her select clique of pupils during the turbulent 1930s now forms part of contemporary popular culture. After presenting a quick panorama of the author and the work, this article adopts a bipartite approach to describe the role of food at different junctures in the narrative. Initially, it focuses on the types of foods presented and the occasions where they are served (for example, as high teas), thereby seeking to outline whether any wider literary symbolism can be detected. Subsequently, the article examines the unusual role of food and foodstuffs in Miss Brodie’s romantic relationship with Mr Lowther, the school’s music teacher, a liaison which is ostensibly centred around her focus on him consuming large quantities of food in order to gain weight. These two sets of food-related observations are then interpreted, analysed, and summarised before further suggestions for additional research on the topic are outlined.